2016
DOI: 10.1007/s12593-014-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of the ALT Flap and Lateral Femoral Cutaneous Nerve for the Reconstruction of Carpal Soft Tissue and Ulnar Nerve Defects: a Case Report

Abstract: The anterolateral thigh (ALT) flap has become one of the workhorse flaps, with indications including diverse reconstructive problems. The lateral thigh area is also a useful donor site for nerve grafts. The lateral femoral cutaneous (LFC) nerve can be dissected along with the ALT flap for a substantial length, depending on the requirements of the recipient site. The LFC nerve can be used as a vascularized or non-vascularized nerve graft. The technique offers advantages and it can find clinical applications, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Combined nerve and soft tissue reconstruction using a free ALT flap with the LFCN has been reported. [5][6][7] Yamamoto et al 5 reported a case using a free ALT flap with vascularized LFCN for treatment of recurrent carpal tunnel syndrome with severe pain due to large neuroma. Villarreal et al 7 reported a case using an extended free ALT flap with vascularized LFCN for the reconstruction of complex neck, head and facial nerve defects following total parotidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Combined nerve and soft tissue reconstruction using a free ALT flap with the LFCN has been reported. [5][6][7] Yamamoto et al 5 reported a case using a free ALT flap with vascularized LFCN for treatment of recurrent carpal tunnel syndrome with severe pain due to large neuroma. Villarreal et al 7 reported a case using an extended free ALT flap with vascularized LFCN for the reconstruction of complex neck, head and facial nerve defects following total parotidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…lateral en el muslo ha permitido, como opción reconstructiva, el desarrollo de los colgajos del músculo tensor de la fascia lata y del colgajo anterolateral del muslo. 1,2 Este colgajo anterolateral se compone de piel y tejido adiposo subcutáneo de la cara anterolateral del muslo, el cual puede proporcionar una extensa área cutánea cuyas dimensiones varían de 25 a 35 cm; además, se puede lograr un colgajo sensitivo al incluir el nervio cutáneo femoral lateral (L2 y L3), conocido también como nervio cutáneo lateral del muslo o nervio femorocutáneo, que sigue un trayecto oblicuo hacia la espina iliaca anterosuperior que pasa en la profundidad del ligamento inguinal hacia el muslo, dividiéndose en los ramos anterior y posterior. 3 Los ramos anteriores emergen a la superficie en un punto situado aproximadamente 10 cm distal al ligamento inguinal e inervan la piel de las porciones lateral y anterior del muslo.…”
Section: Introductionunclassified